Synthesis of Glycerol Homologues - Thota, Kiran Kumar; Trudell, Mark L. (Synthesis, 2013)
A series of monoprotected glycerol homologues and triols were prepared in high overall yields (>90%) via the hydroboration–oxidation of the corresponding dienols. Hydroboration with disiamylborane and concomitant alkaline oxidation (NaOH, H2O2) was found to be a mild, high-yielding, and highly efficient method for the construction of a variety of glycerol homologues.
Keywords: hydroboration; diols; triols; diene; disiamylborane